Fabrication of a Gas Sensor from Thin Films of Tungsten Oxide Nanoparticles and Their Use in Oil Refineries - Jebur, Khalid. H. (Journal of Petroleum Research and Studies, 2022)
In this research, the structural and sensitivity properties of the toxic gases of films tungsten oxide (WO3) nanoparticles prepared by the pulsed laser deposition method were manufactured and studied using a Nd:YAG laser. To show the effect of different temperatures (400, 600 and 800 oC) on films deposited on quartz substrate for all samples. The results of X-Ray diffraction (XRD) showed that all the thin films have polycrystalline structure and have a peak direction (010) for all samples, and that increasing the temperature led to an increase in the particle size. The decrease in the values ​​of the full width and half maximum (FWHM) of the films (WO3) for (010) modes from 0.19 to 0.14 with increasing temperature. The nature of the topography of tungsten oxide (WO3) nanoparticles was studied using atomic force microscopy (AFM), which proved that the films grown in this way have good crystallization and have a homogeneous surface. The root mean square (RMS) values ​​of the tungsten oxide nanoparticles (WO3) increases with increasing temperature. When measuring the sensitivity of tungsten oxide nanoparticles (WO3) to (CO, NH3 and NO2) gases, it was found that the films have good sensitivity to these gases at room temperature (RT), and it was the best sensitivity of the films is at a temperature of (800 oC) as follows: CO gas (81%), NH3 gas (84%) and NO2 gas (100%) .All studies have shown that tungsten oxide (WO3) has the ability to detect toxic gases, such as (CO, NH3 and NO2), which have an detrimental effect on workers in oil refineries. The films of tungsten oxide (WO3) is used in themanufacture of gas sensors that can be used inthese refineries, and when the temperature increases, it becomes more sensitive to gases (CO, NH3, NO2).